DIPLOMASI EKONOMI INDONESIA DALAM MENINGKATKAN EKSPOR KAKAO KE MALAYSIA PERIODE 2017 – 2021 - Putri, Melisa Triatika Putri; Darmastuti, Shanti; Salam, Syahrul (Mandala: Jurnal Ilmu Hubungan Internasional, 2025)
Indonesia is one of the countries that relies on international trade to support its economic growth. Since the 1980s, Indonesia's international trade has undergone significant changes, where previously, its exports heavily depended on oil and gas commodities. However, non-oil and gas commodities, such as cocoa, have now become dominant sectors in Indonesia's export development. Exports play a vital role in a country's economy, as an increase in exports compared to imports benefits the country, while dependence on imports can lead to a trade balance deficit. Malaysia is one of the main destinations for Indonesia's cocoa exports, followed by China, India, the United States, and the Philippines. Total cocoa exports in the last five years have shown fluctuations. Although geographically close, there are significant differences between Indonesian and Malaysian cocoa beans, especially in processing practices, particularly cocoa bean fermentation. Studies have shown that Indonesia's cocoa exports to Malaysia have increased, although from 2017 to 2021, there was a slight decline in the export volume. Indonesia's economic diplomacy, including cocoa product promotion and production quality improvements, has played a crucial role in maintaining and enhancing the competitiveness of Indonesian cocoa in the Malaysian market. Overall, Indonesia's economic diplomacy has significantly contributed to boosting cocoa exports to Malaysia during the 2017–2021 period through various initiatives that strengthen the competitiveness and quality of Indonesian cocoa products in the international market.